Importance of Monitoring Mass Tourism for Sustainable Development in Bangladesh - Sarker, Jashim Uddin (Asian Business Review, 2016)
Tourism is a buzzword worldwide at present days. Bangladesh is also a beneficial country like many others in the world since this country is full of potentials with natural resources and tourism industry. Tourism often seems a blessing for the nation. However, mass tourism has both useful and harmful impacts on a country like Bangladesh. Sometimes the rate of negative consequences is higher than the positive ones. Mass tourism brings dangerous results to the local economy, community, culture and environment of a country. However, these dangers can be lessened through proper monitoring, investigation and appropriate interventions of the government as well as other private agencies. This paper explores both the good and bad effects of mass tourism. It also analyzes the significance of effectively monitoring mass tourism so that benefits outweigh the risks.